Clinical and Microbiological Characteristics of the State of Vaginal Biocenosis among Patients with Preterm Labor - A. V. Sergeeva; N. Yu. Katkova; O. I. Bodrikova; O. V. Kovalishena; I. M. Bezrukova; K. B. Pokusaeva (Эпидемиология и вакцинопрофилактика)
Relevance. Premature birth (PR) in the etiopathogenetic relationship is a clinical syndrome characterized by polyetiology, a chronic course of the process, the participation of the fetus in pathogenesis, a variety of clinical symptoms, and the involvement of genetic and environmental factors. The infectious factor is considered as the leading risk for the development of PR. According to the literature, more than 40% of PR is due to the presence of an infectious process. The most significant are intrauterine and cervical vaginal infections. Purpose of the study was a clinical and microbiological assessment of the state of the vaginal biotope in women with various options for spontaneous preterm birth.Materials and methods. The diagnostic complex included bacterioscopic, bacteriological, and also molecular genetic studies. The object of the study was pregnant women with timely physiological delivery and with various types of preterm birth, who were hospitalized in specialized medical organizations of the Nizhny Novgorod region. A total of 260 patients were examined, and 1000 studies were conducted. Material for research was the contents of the vagina and cervical canal.Results. The state of the vaginal biocenosis was characterized by pronounced irregularity in patients with different variants of spontaneous preterm birth. In women with premature rupture of the membranes, a local inflammatory process with the prevalence of conditionally pathogenic microflora over lactic acid bacteria was significantly frequent. Lactoflora prevailed among patients with true PR and with timely physiological labor in the composition of the vaginal biotope. In women with preterm labor with isthmic-cervical insufficiency, there were mixed disorders of the vaginal biocenosis.Conclusions. The risk of developing spontaneous preterm birth is reliably determined by the state of the vaginal biocenosis.